“Well Disposed Towards the Self and the World”: In Conversation with Daya Dissanayake - Amit Bhattacharya (Asiatic: IIUM Journal of English Language and Literature, 2025)
This interview explores Daya Dissanayake’s moral vision, socio-cultural concerns, and creative credo. He discusses his latest novel The Sacred Grove (2024) and highlights his use of non-human and posthuman narrators. Dissanayake explains how bilingualism has enriched his work, as he extols digital creativity, a research mindset, a pluralistic outlook, and environmental awareness. The writer critiques the Eurocentric concept of nationalism and the lingering influence of imperialism on Sri Lankan identity, pleading for a more inclusive and eco-sensitive mindset. He also expresses his indebtedness to India’s cultural and literary heritage as a shaping influence on his sensibility. While he consciously avoids overt references to conflicts in his works, he offers a nuanced perspective on the Sri Lankan Civil War (1983 – 2009). He champions open-access publishing and lenient copyright laws and explores issues like family relationships, man-nature interactions, the gender question, the role of memory, and the need for non-violence. His scant poetic output and infrequent forays into non-fiction come under the scanner. As a votary of Subhashita Sahitya (morally responsible literature) Dissanayake regards universal well-being as his intended literary message. The interview ends with the author’s revelation of his future literary plans.